(untitled) (Research, Society and Development, 2020)
The aim of this work was the integral application of jabuticaba peel to obtaining a crystallized jabuticaba peel by osmotic dehydration, crystallization and convective drying at different temperatures. Every two months for a year, the product was subjected to determinations of anthocyanins, phenolic compounds, antioxidant capacity, physicochemical characteristics and determination of color. The color measurements and bioactive compounds determinations were significantly influenced by the interaction between the factors drying temperature and storage time. The proximal composition was not affected by drying temperature, whereas total soluble solids, pH, titratable acidity and water activity showed significant differences. Crystallized jabuticaba peel is a low cost product and viable alternative to minimize the large losses during the harvest season.